Durability of mixed mortar lining containing dregs-grits - Zanella, B. P. [UNESP]; Sá, E. B. [UNESP]; Acorinti, N. O. [UNESP]; Trannin, I. C.B. [UNESP]; Simões, S. J.C. [UNESP] (Science Publications, 2014)
The improper disposal of industrial waste and exploitation of natural resources has resulted in the scarcity of river sand and environmental degradation, such as river erosions and pollution. This study aimed to assess the durability of mixed mortar lining walls and ceilings, containing 0 (default), 10 and 20% of dregsgrits compounds-waste of the pulp industry-in substitution with river sand. This was done with tests that simulated both natural and artificial conditions: Direct solar incidence (testing ultraviolet radiation), attack by spraying solution (salt spray test), natural warming of the walls and ceilings incidence by indirect solar (thermal degradation) and residential fires (thermogravimetric test), in compliance with both national and/or international standards. The grout containing dregs-grits compounds showed similarity to standard (0%) for testing thermal degradability, thermogravimetric and ultraviolet radiation, but shows significantly less durability when exposed to salty environments. © 2013 Science Publication.
Keywords: Industrial waste; Recycling; Salt spray; Thermogravimetric; Ultraviolet radiation